What defines a great surgeon? A survey study confronting perspectives - Luscan, Romain; Malheiro, Emeline; Sisso, Fiona; Wartelle, Sébastien; Parc, Yann; Fauroux, Brigitte; Bégué, Thierry; Johanet, Hubert; Denoyelle, Françoise; Garabédian, Erea-Noël; Simon, François (Frontiers in Medicine, 2023)
Background The definition of a great surgeon is usually reported by surgeons themselves. The objective of the study was to define a multifaceted definition of a great surgeon, by confronting patients', healthcare workers', and surgeons' perspectives. Study design An online open-ended questionnaire was created to identify three qualities and three shortcomings defining a great surgeon. Age, gender, and profession of respondents were collected. Responses with a similar meaning were combined into word groups and labeled within four themes: human qualities, technical surgical skills (TSS), non-technical skills (NTS), and knowledge. Multivariate analyses were conducted between themes and respondent characteristics. Results Four thousand seven hundred and sixty qualities and 4,374 shortcomings were obtained from 1,620 respondents including 385 surgeons, 291 patients, 565 operating theater (OT) health professionals, and 379 non-OT health professionals. The main three qualities were dexterity (54% of respondents), meticulousness (18%), and empathy (18%). There was no significant difference between professional categories for TSS. Compared with surgeons, non-OT health professionals and patients put more emphasis on human qualities (29 vs. 39% and 42%, respectively, p < .001). OT health professionals referred more to NTS than surgeons (35 vs. 22%, p < 0.001). Knowledge was more important for surgeons (19%) than for all other professional categories (p < 0.001). Conclusions This survey illustrates the multifaceted definition of a great surgeon. Even if dexterity is a major quality, human qualities are of paramount importance. Knowledge seems to be underestimated by non-surgeons, although it essential to understand the disease and preparing the patient and OT team for the procedure.